Retrospective analysis of preoperative serum tumor marker levels and their correlation with pathological characteristics and prognosis in cervical cancer patients - Shen, Yue; Kang, Min (Frontiers in Genetics, 2026)
ObjectiveTo investigate the relationship between the levels of preoperative serum tumor markers SCC-Ag, CEA, and CA125 and pathological characteristics in cervical cancer patients, and to analyze their predictive value for prognosis.MethodsA retrospective analysis was conducted on clinical data from 82 patients with cervical cancer (cervical cancer group), 98 patients with benign cervical lesions (benign lesion group), and 80 healthy controls (healthy control group). Serum tumor marker levels were compared among the three groups to evaluate their diagnostic value for cervical cancer. Differences in tumor marker levels were assessed among cervical cancer patients with varying TNM stages, differentiation degrees, and pathological types. Pre-treatment tumor marker levels were also compared between patients with different prognoses.ResultsPatients in the cervical cancer group exhibited significantly higher levels of SCC-Ag, CEA, and CA125 compared to the benign lesion and healthy control groups (P < 0.05). The AUCs of the three markers for diagnosing cervical cancer were 0.8338, 0.8379, and 0.8466, respectively (P < 0.0001). Tumor marker levels showed an increasing trend with advancing TNM staging and decreasing differentiation degree (P < 0.05). Patients with squamous cell carcinoma had significantly higher SCC-Ag levels, while those with adenocarcinoma had significantly higher CEA and CA125 levels (P < 0.05). At 2-year follow-up, the recurrence group exhibited significantly higher tumor marker levels before treatment compared to the non-recurrence group (P < 0.05).ConclusionSerum levels of SCC-Ag, CEA, and CA125 are closely associated with the pathological characteristics of cervical cancer, demonstrating high diagnostic value. Pre-treatment tumor markers levels serve as important reference indicators for prognostic assessment.